Performance of a seawater-driven forward osmosis process for pre-concentrating digested sludge centrate: organic enrichment and membrane fouling. Issue 7 (6th June 2018) - Vu, Minh T.; Ansari, Ashley J.; Hai, Faisal I.; Nghiem, Long D.
Abstract : This study demonstrated the potential of seawater-driven forward osmosis for enriching organic matter in digested sludge centrate. Abstract : This study demonstrated the potential of seawater-driven forward osmosis for enriching organic matter in digested sludge centrate. The results indicated that the cellulose triacetate membrane offered better performance than the polyamide membrane in terms of organic materials enrichment, fouling resistance and membrane cleaning efficiency. Membrane fouling decreased the enrichment efficiency of organic matter since the deposition of suspended particulate matter on the membrane surface caused fouling and loss of organic matter from the concentrated sludge centrate. The results showed that increasing the draw solution concentration increased flux but did not aggravate membrane fouling, however, it could reduce the efficiency of physical flushing to recover the flux. Seawater showed comparable forward osmosis performance to that of analytical grade NaCl as draw solutes in terms of flux and organic enrichment. The results also showed that seawater as the draw solution resulted in more membrane fouling and lower flux recovery compared to NaCl.